THE REALISATION OF ADVICE SPEECH ACT - Sulaymanova Nilufar (International Journal of Literature and Language Studies, 2026)
Abstract. This article states that the illocutionary goal is a phenomenon that motivates the formation of the content of a specific speech act, that the illocutionary goal is manifested depending on the situation and becomes a source of determining the communicative content of this event (communicative implicature), that the illocutionary goal expressed through the advice speech act is based on the desire to encourage the interlocutor to perform a certain action, and that there is a positive evaluation component in its content.